The Role of Digital Technologies in Teaching and Learning of English Language (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study offers the findings of an investigation into the use of digital tools in languageclassrooms, with a focus on the English language. The goals included discovering how often and in whatways students use digital communication to learn English, as well as exploring the types of digitalcommunication students use to learn English. Finding out what kinds of digital communication studentsuse and how they use them to study English was another goal, as was identifying the barriers thatstudents confront when attempting to use such tools for language study. The research strategy for thisstudy will be descriptive analytical. The method is an exploratory sequential design in which qualitativedata is gathered analyzed to draw conclusions about the relationship between two variables. Thefindings indicate that digital communication has an impact on language development, particularlyEnglish, if the necessary resources are made available technical issues are resolved.